Mapping the Unique Tree Species in Tambora National Park for The Development of Eco-Tourism- Based Science Modules - I Gde Mertha; Agil Al Idrus; M. Sarjan; Aliefman Hakim; Joni Rokhmat; AA Sukarso; Deni Rahadi; I Nengah Korja; Rangga Alif Faresta (Postgraduate Program, University of Mataram, 2024)
The objective of this research is to map the unique tree species composing the vegetation in the tropical, sub-mountain, and mountain zones of Tambora National Park. This study is essential for the development of teaching materials, specifically eco-tourism-based science modules, which have been implemented in Tambora National Park. Data collection was carried out on four hiking trails: Kawinda Toi, Doro Ncanga, Piong (Kore), and Pancasila. The data collection techniques used namely plot transects and exploration methods. The results showed that in the tropical zone (1-1000 m asl), the dominant tree species were pato (Buchacania sessifolia) with an Importance Value Index (IVI) of 41.86%, monggo putih (Syzigium sp.) with an IVI of 34.00%, and monggo merah (Syzigium polyanthum) with an IVI of 33.80%. In the sub-mountain zone (1000-2000 m asl), the dominant species were cemara gunung (Casuarina junghuhniana) with an IVI of 44.50%, sarume ara (Acronychia trifoliata) with an IVI of 40.23%, sarou (Engelhardtia spicata) with an IVI of 40.19%, and kosok (Myrsine avenis) with an IVI of 38.75%. In the mountain zone (above 2000 m asl), the dominant species was cemara gunung (Casuarina junghuhniana) with an IVI of 300%. Endemic species identified included Elaeocarpus batudulangii (endemic to Nusa Tenggara) and Parachidendron pruinosum var. sumbawaense (endemic to Sumbawa Island). The populations and distribution of these endemic species are very limited. Other noteworthy species include klanggo (Duabanga moluccana), sori hitam (Syzigium acuminatissimum), and sori putih (Syzigium racemosum). The output of this research is a science module in the form of a Field Guide and booklet based on eco-tourism interpreting the unique forest trees for teaching ecosystem materials in secondary schools and as a guide for tourists, as well as providing information for the management of Tambora National Park in West Nusa Tenggara.